RYNEK PRACY W OPINIACH STUDENTÓW - Kowalczyk, Elżbieta (Wydział Prawa i Administracji UAM, 2003)
In her article the author presents the opinions of students concerning their professional career opportunities. Young people on the threshold of their professional careers have to face the necessity of negotiating over their jobs - a task particularly difficult in the situation of a crisis on the labour market. Those negotiations are understood as a configuration of specific talks held by two sides: - an employer, purchasing particular goods such as labour, — an employee, offering his abilities and devotion. Their mutual relations dictate supply and demand for labour, which undergoes business cycles. In order to explain this market process, the author constructed and conducted two-staged research. In the first stage, a sample of students was presented with a description of the labour market and asked to discuss career opportunities on the described market. At the next stage they were requested to describe their preparations for undertaking professional activities and focused mainly on the strengths and weaknesses of actors on the labour market. The analysis of the research results in the following article may help to understand fears and hopes of young people and to prepare an effective program which could facilitate finding a place on the increasingly demending labour market.
LABOUR MARKET IN STUDENTS’ OPINIONS